2002
DOI: 10.1093/rheumatology/41.9.988
|View full text |Cite
|
Sign up to set email alerts
|

Increased levels of autoantibodies against copper-oxidized low density lipoprotein, malondialdehyde-modified low density lipoprotein and cardiolipin in patients with rheumatoid arthritis

Abstract: RA patients had increased levels and prevalence of autoantibodies against CL, oxLDL and MDA-LDL, with associations to severity of disease and cardiovascular complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 45 publications
1
21
0
1
Order By: Relevance
“…124 aPLs as well as antibodies against OxLDL are raised in RA, but their clinical importance for CVD and atherosclerosis is not clear in this context and is likely to be complex. 125 Also in RA, lipid peroxidation may play a role, and interestingly, OxLDL-containing foam cells have been detected in synovia from RA patients. 126 Also interesting, HSPs are implicated in RA and atherosclerosis, although immune reactivity to HSPs in RA appears to play a somewhat different role, being protective in many cases.…”
Section: Ra and Other Autoimmune Conditions In Relation To Atherosclementioning
confidence: 99%
“…124 aPLs as well as antibodies against OxLDL are raised in RA, but their clinical importance for CVD and atherosclerosis is not clear in this context and is likely to be complex. 125 Also in RA, lipid peroxidation may play a role, and interestingly, OxLDL-containing foam cells have been detected in synovia from RA patients. 126 Also interesting, HSPs are implicated in RA and atherosclerosis, although immune reactivity to HSPs in RA appears to play a somewhat different role, being protective in many cases.…”
Section: Ra and Other Autoimmune Conditions In Relation To Atherosclementioning
confidence: 99%
“…Thus, it is not surprising that an association was found between the presence of anti-oxLDL antibodies and atherosclerosis and CVD. [25][26][27][28][29][30][31] OxLDL as an Agent in the Development of Atherosclerosis and CVD LDL can be oxidatively modified in vivo to be an immunogen associated with the progression of atherosclerosis and CVD. 32,33 In a study using a mouse model of experimental antiphospholipid syndrome (APS), mice immunized with oxLDL exhibited a significantly more severe form of the disease compared with native LDL-immunized mice, as expressed by lower platelet counts, longer activated partial thromboplastin time, and higher fetal resorption rates.…”
Section: Oxldl: a Notorious Molecule That Maymentioning
confidence: 99%
“…Elevated levels of anti-oxLDL antibodies were found in patients with autoimmune diseases, including rheumatoid arthritis, systemic lupus erythematosus, and APS, 16,26,30,[72][73][74][75][76][77][78][79][80][81][82][83][84] as well as in other conditions such as diabetes mellitus, 71 uremia, 77 chronic periaortitis, hepatocellular carcinoma, ␤-thalassemia, psoriasis, and preeclampsia and eclampsia (Table 2).…”
Section: Pathogenic Role Of Anti-oxldl Antibodies In Humansmentioning
confidence: 99%
“…It has been suggested that anti-oxLDL antibodies might possess pathogenic as well as protective effects (5). The pathogenic effects of anti-oxLDL antibodies is supported by observations of elevated IgG seen in lesions (6) in the sera of patients with coronary disease (7,8), peripheral vascular disease (9), and with syndromes associated with accelerated atherosclerosis such as hypertension, diabetes, and immune-mediated diseases (e.g., rheumatoid arthritis, systemic lupus erythematosis) (10,11). However, others have speculated that the See page 2313 higher levels of anti-oxLDL antibodies, in particular IgM autoantibodies, observed in children compared with levels in adults might serve a protective purpose.…”
mentioning
confidence: 98%